Analysis of the Effect of Performance Expectancy, Effort Expectancy, and Lifestyle Compatibility on Behavioral Intention QRIS in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2022)
The important objective of this study is to analyze the effect of performance expectancy, effort expectancy, and lifestyle compatibility on behavioral intention toward QRIS in Indonesia. The data collected in this study are quantitative data using a quantitative approach. The population in this study is MSME actors in Indonesia, and the sample obtained using the convenience sampling method was as many as 140. Data analysis used instrument tests, normality tests, regression tests, hypothesis tests, correlation tests, and the coefficient of determination. The results showed that performance expectancy and lifestyle compatibility positively and significantly affected behavioral intention. At the same time, the other results show that effort expectancy has a positive but insignificant effect on behavioral intention. The study’s conclusion confirms that to increase the enthusiasm of MSME actors to use QRIS as an alternative to non-cash payments, the government and relevant stakeholders need to conduct in-depth socialization regarding the benefits and advantages of using QRIS for MSME actors. Furthermore, QRIS users must be careful of QR code counterfeiting by irresponsible parties and sabotage of QR Code user accounts which lead to cyber crime